Cassava masala in the peruvian amazon: Empirical fermentationtechnology, nutritional value, and cultural relevance - Buendía Molina, Marilyn Aurora (2025)
Masato de yucca is a traditional-fermented beverage from the Peruvian Amazon, made mainly byindigenous communities such as the Shipibo- Konibo, Asháninka and Awajún. Its ancestral preparation involves the fermentation of cooked yucca, often initiated by chewing the tuber, a process that activates salivary enzymes that convert starches into fermentable sugars. This review article analyzesaspects of its fermentation, nutritional profile, cultural relevance and socioeconomic potential.importance lies in preserving this practice as part of cultural heritage and discussing the opportunitiesand challenges of its valorization in contemporary contexts.